The Behavior of Interest Rates - Fama, Eugene F. (Review of Financial Studies, 2006)
The evidence in Fama and Bliss (1987) that forward interest rates forecast future spot interest rates for horizons beyond a year repeats in the out-of-sample 1986–2004 period. But the inference that this forecast power is due to mean reversion of the spot rate toward a constant expected value no longer seems valid. Instead, the predictability of the spot rate captured by forward rates seems to be due to mean reversion toward a time-varying expected value that is subject to a sequence of apparently permanent shocks that are on balance positive to mid-1981 and on balance negative thereafter. Copyright 2006, Oxford University Press.